Programa pedagógico “Viviendo en Armonía” para desarrollar las Habilidades Sociales básicas, de los estudiantes del segundo grado de Educación Primaria de la Institución Educativa “Alexander Von Humboldt”-Trujillo, 2015 - Huatay Oliva, Karen Noheli (2017)
The present research aims to determine the extent to which the application of the pedagogical program "living in harmony", develops the basic social skills of the students of the second grade of primary education of the I.E. "Alexander Von Humboldt" of Trujillo in the year 2015._x000D_ The research design employed was quasi experimental and a sample of 55 students was studied, 28 belonged to the experimental group and 27 to the control group._x000D_ The "living in harmony" pedagogical program was aimed at developing basic social skills of making friends, knowing how to converse, expressing feelings and making decisions._x000D_ It was concluded that the pedagogical program "living in harmony" significantly influences the development of basic social skills of the students of the second grade of primary education of the Educational Institution "Alexander Von Humboldt" in Trujillo, in the year 2015.